When monoculture leads to monofailure. - Zuckerman, Ethan (Prospect, 2024)
On July 19th, a routine update by cybersecurity company CrowdStrike caused widespread computer failures, affecting 8.5 million systems worldwide. The reliance on a single operating system, Microsoft Windows, and a single threat checker, CrowdStrike, for critical commercial IT systems makes global outages possible. This monoculture vulnerability is similar to the risks associated with monoculture farming, where planting a single crop can lead to devastating consequences if a disease or pest strikes. The article suggests that diversifying technical ecosystems, like polyculture farming, could lead to more resilient systems.